The research of role of non ureotelic arginases in polyamines biosynthesis in brain and kidney in vitro - N. V. Avtandilyan (ՀՀ ԳԱԱ հրատ.)
Currently the investigation of the role of arginase isoforms in biosynthesis of polyamines is an issue of key importance. The real source of ornithine for synthesis of polyamines has not been clearly defined yet. Արգինազի իզոէնզիմների դերի պարզաբանումը պոլիամինների կենսասինթեզում հանդիսանում է արդիական հարցերից մեկը: Роль изоферментов аргиназы в биосинтезе полиаминов является актуальным вопросом. Еще не определен реальный источник орнитина для синтеза полиаминов. Целью работы было изучение влияния эндогенных и экзогенных полиаминов на активность неуреотелической аргиназы (НУА) головного мозга и почек in vitro.
Keywords: Biology; Biochemistry